URGENSI KEBIJAKAN PROGRAM BEUT AL-QUR’AN BA’DA MAGRIB TERHADAP PENINGKATAN LITERASI AL-QUR’AN BAGI ANAK USIA SEKOLAH DI ACEH BESAR - Mujiburrahman Mujiburrahman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Observing the phenomenon of shifting similarity, especially in the cultural aspects of recitation (beut) of the Qur'an in the prevention of community life. The Aceh Besar District Government is based on the value of dedication and moral responsibility to intervene through a breakthrough and policy on Beut Al-Qur'an Ba'da Magrib (BABM) Program. The implementation of BABM refers to two main foundations: First, the socio-cultural foundation, in which the seumeubet tradition has been deeply rooted in the Acehnese society carried out in meunasah, mosques, balee seumeubeut or in private homes. Second, the juridical basis, in the form of Law No. 11 of 2016 on the Government of Aceh, and the Regulation of the Regent of Aceh Besar. 53 of 2012 on Guidelines for Implementation Beut Al-Qur'an Ba'da Magrib In Aceh Besar District. The BABM program, which has been running for five years since it was launched in 2012 and continues to date in 604 gampongs in Aceh Besar District, has received good results. First, the BABM program has yielded good results on the development and improvement of the literacy of al-Qur'an for school-aged children in Aceh Besar. Second, the BABM program also has a positive impact on increasing religious understanding among school-aged children through the addition of a number of religious teaching materials taught in BABM programs, as well as changing their character better than ever. Third, through the implementation of the BABM program has also fostered the spirit of religious practice among the community, while reducing the negative impacts and criminality in the community.